Performance and Emission Characteristics of a Ci Engine Fueled With Nanodiesel - M., Ghanbari; G., Najafi; B., Ghobadian; R., Mamat; M. M., Noor (2015)

(untitled)
The purpose of this study is to experimentally analyse the performance and the exhaust emissions of a diesel engine operating on nanodiesel blended fuels. Multi wall carbon nano tubes (CNT) (40, 80 and 120 ppm) and nano silver particles (40, 80 and 120 ppm) with nano-structure were produced and added as additive to the diesel fuel. Six cylinders, four-stroke diesel engine was fuelled with these new blended fuels and operated at different engine speeds. Experimental test results indicated the fact that adding nano particles to diesel fuel, increased diesel engine performance variables including engine power and torque output. For nano-diesel it was found that the brake specific fuel consumption (bsfc) was decreased compared to the net diesel fuel. The results showed that with increasing of nano particles concentrations at diesel fuel, CO2 emissions increased. CO emission in diesel fuel with nano-particles was lower significantly compared to pure diesel fuel. UHC emission with silver nano-diesel blended fuel decreased while with fuels that contains CNT nano particles increased. The trend of NOx emission was inverse compared to the UHC emission. With adding nano particles to the blended fuels, NOx increased compared to the net diesel fuel. The tests revealed that silver & CNT nano particles can be used as additive in diesel fuel to improve complete combustion of the fuel and reduce the exhaust emissions significantly.